Morphometric study for the intracranial portion of the vertebral artery in human cadavers - Zeel Patel; Ali Abdulsattar Abdulrahman (Elsevier, 2020)
Among posterior circulation arteries, the intracranial vertebral artery (ICVA) has been given the least attention, especially concerning treatment of occlusive lesions. Early clinicopathological studies showed that the ICVA was often occluded in patients with lateral medullary and posterior inferior cerebellar infarcts. Therefore, identification and description of ICVA variations existing in length, degree of union of the left & right vertebral arteries is crucial as it accounts for the arterial blood delivery to the hindbrain and will be more displayed if pathologies exist. Cerebral angioarchitecture is so valid in interventional radiology to address diagnosis as well for neurosurgeons.Ten human formalin fixed brain specimens obtained from cadavers, donated for study purpose, were under examination in the Department of Biology at Chatham University (Pittsburgh, Pennsylvania). Dissection procedure was undertaken according to the dissection manual Grant dissector, with modifications. Variations existing in length, degree of union of left & right vertebral arteries using the digital Vernier caliper, were observed with a magnifying glass. Results indicate the mean external diameter as 3.72 mm for the LVA and 3.79 mm for the RVA. The angle between LVA & RVA ranged from 51° degrees to 91° degrees. There is a significant correlation between the angle and the differences in the external diameter of the LVA & RVA [r = −0.656, n = 10, p = 0.0394]. These factors play a crucial role in the arterial blood delivered to the hindbrain and will be more displayed if pathologies exist.